Analysis of Art Museum Design under the Concept of Sustainable Development (American Journal of Arts and Human Science, 2024)
With the rapid growth of economy and urbanization, the development of cities has gradually focused on promoting the culture and image of cities and meeting the spiritual needs of the people. Therefore, cultural public buildings play an important role in urban development. However, the process of urbanization has led to the gradual saturation of urban architectural space. Cultural public buildings must not only meet the development requirements of cities, but also have the sustainability of development advocated by society and the diversity of use functions. On this basis, this article takes spatialism as a design approach and urban art gallery space as a design carrier to summarize the characteristics of green, low-carbon and sustainable development pursued by urban development under the spatialism design idea. This article discusses the overall situation from large to small, from far to near, summarizes the corresponding design ideas, and uses a large number of cases to support the relevant design ideas, aiming to explore the research on the architectural space design of art galleries that is both in line with the sustainability of urban development and in line with the aesthetics of modern people in architectural space.